The ‏Relationship ‏between ‏Emotional ‏Intelligence ‏and ‏Social ‏Adjustment ‏of ‏Students - Meraban Parsamehr; elahe heddat (توسعه اجتماعی, 2017)
Social ‏adjustment ‏in ‏adolescents ‏is ‏as ‏the ‏most ‏important ‏symptom ‏of ‏their ‏health ‏which ‏some ‏factors ‏like ‏Likewise ‏Emotional ‏Intelligence ‏effective ‏in ‏its ‏creation .This ‏study ‏aimed ‏to ‏measure ‏the ‏relationship ‏between ‏emotional ‏intelligence ‏and ‏social ‏adjustment ‏among ‏student ‏with ‏the ‏survey ‏method ‏and ‏407 ‏students ‏of ‏Yazd ‏University ‏were ‏selected ‏by ‏using ‏simple ‏random ‏sampling ‏and ‏standard ‏questionnaires ‏were ‏distributed. ‏Findings ‏of ‏Pearson ‏correlation ‏shows ‏the ‏relationship ‏between ‏Emotional ‏Intelligence ‏and ‏the ‏step ‏by ‏step ‏regression ‏go ‏forward ‏to ‏four ‏step ‏and ‏its ‏results ‏showed ‏that ‏are ‏able ‏to ‏explain ‏35% ‏social ‏adjustment ‏of ‏students. ‏The ‏results ‏of ‏this ‏study's ‏findings ‏according ‏to ‏Bar-On, ‏phenomenology ‏and ‏Rogers ‏theories ‏suggest ‏that ‏there ‏is ‏direct ‏relation ‏between ‏emotional ‏intelligence ‏and ‏it ‏was ‏found ‏that ‏social ‏adjustment ‏among ‏the ‏students ‏and ‏reinforcement ‏of ‏the ‏emotional ‏intelligence ‏in ‏different ‏degrees ‏due ‏to ‏higher ‏adjustment ‏to ‏environment ‏and ‏friends.